2003
DOI: 10.1088/0953-8984/15/33/103
|View full text |Cite
|
Sign up to set email alerts
|

High aspect ratio piezoelectric strontium–bismuth–tantalate nanotubes

Abstract: We report the deposition and characterization of transparent ferroelectric/piezoelectric nanotubes of wall thickness about 40 nm, tube diameters ranging from a few hundred nanometres to 4 µm, and length about 100 µm.Comparison with other nanotubes is made and applications in dynamic random access memory trenching and ink-jet printers are discussed. 1 [3] claims piezoelectric nanotubes of boron nitride deposited on top of SiC cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…The substantial progress in synthesis of various ferroelectrics nanosystems, like epitaxial films [4], nanoparticles with controllable sizes [5], arrays of tubes and rods [6][7][8][9], the local characterization of their polar properties [10][11][12] and domain structure [13], triggered the renovation of interest to ferroic nanosystems theoretical description. It is worth to note the enormous achievements of both the phenomenological [14] and microscopic [15] theories, their recent advances in different fields like the description of nanorods [16,17], size effects in thin films [18,19], ferroelectric nanoparticles [20][21][22]; flexoelectric effect influence on the intrinsic properties [23,24] and response [25][26][27] of the nanosystems; the developed analytical model accounting for depolarization field as well as the formation of misfit dislocations [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The substantial progress in synthesis of various ferroelectrics nanosystems, like epitaxial films [4], nanoparticles with controllable sizes [5], arrays of tubes and rods [6][7][8][9], the local characterization of their polar properties [10][11][12] and domain structure [13], triggered the renovation of interest to ferroic nanosystems theoretical description. It is worth to note the enormous achievements of both the phenomenological [14] and microscopic [15] theories, their recent advances in different fields like the description of nanorods [16,17], size effects in thin films [18,19], ferroelectric nanoparticles [20][21][22]; flexoelectric effect influence on the intrinsic properties [23,24] and response [25][26][27] of the nanosystems; the developed analytical model accounting for depolarization field as well as the formation of misfit dislocations [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The ferroelectric phase was studied in ferroelectric nanowires, nanotubes and nanorods [1], [2], [3], [4], [5]. It is appeared that nanorods and nanowires posses such polar properties as remnant polarization and piezoelectric hysteresis [1], [2], [5].…”
Section: Introductionmentioning
confidence: 99%
“…10,11,[30][31][32][33][34][35] For example, piezoelectric nanotubes with perovskite-structure are used for the construction of 3D memory devices. 36) The hierarchic 3D structures with high storage density have large potentials for a variety of applications in addition to those in ferroelectric memory devices. Moreover, it has recently been found that novel organic-inorganic hybrid liquid crystals could be fabricated by using monodispersed TiO 2 37) or -Fe 2 O 3 38) particles with characteristic morphologies.…”
Section: Shape Control Of Bnt Particles By the Changing Ofmentioning
confidence: 99%